METHODOLOGICAL WAY TO ENSURE SELF-DEVELOPMENT OF CHILDREN AND CAREGIVERS IN THE PROCESS OF PRESCHOOL EDUCATION - Marina G. Grushina; Lilia F. Orlova; Natalya V. Sokolova (Открытое образование (Москва))
For example, the CRD MUNICIPAL budget preschool educational institution – kinder-center “Baby” the results of realization of noospheric educational technologies adapted to the specifics of children’s age. The methodological possibilities of creative tasks, technology use computer environment, heuristic learning, music education, narrative learning. The analysis of the importance of ensuring the professional competence of teachers. The efficiency bioadequate methods of teaching in practical operation the OED. Through psycho-pedagogical monitoring of creative development of a preschool child a study of the effectiveness of the noosphere theory; generalized educational experience from the standpoint of using environmentally friendly means and methods in the system of training and education.